Haemoglobin thresholds for transfusion: how are we doing in the era of Choosing Wisely? A retrospective cohort study (Swiss Medical Weekly, 2023)
INTRODUCTION: Clinical practice guidelines and the Choosing Wisely initiative launched in 2012 recommend a haemoglobin (Hb) threshold of 70–80 g/lfor red blood cell (RBC) transfusions in stable hospitalised patients. Data on transfusion practices and their trends in medical inpatients are limited. To address this gap, we investigated transfusion practices and their trends in general internal medicine and other clinics.METHODS: This retrospective cohort study analysed data from all hospitalisations with RBC transfusions at a Swiss university hospital between 2012 and 2019. We included all first transfusion episodes if pretransfusion Hb was available. The primary endpoint was mean pretransfusion Hb; secondary endpoints included potentially inadequate transfusions (i.e., transfusions at Hb ≥80 g/l) and receipt of a single RBC unit. Trends in mean pretransfusion Hb over time were estimated using generalised estimating equations, and risk factors for potentially inadequate transfusions were identified using multivariable adjusted generalised estimating equations models.RESULTS: Of 14,598 hospitalisations with RBC transfusions, 1980 (13.6%) were discharged from general internal medicine. From 2012 to 2019, mean pretransfusion Hb decreased from 74.0 g/l to 68.8 g/l in general internal medicine (mean annual decrease –0.76 g/l, 95% confidence interval [CI] –0.51 to –1.02) and from 78.2 g/l to 72.7 g/l in other clinics (mean annual decrease –0.69, 95% CI –0.62 to –0.77; p for interaction 0.53). The overall proportion of potentially inadequate transfusions was 17.8% in general internal medicine and 24.1% in other clinics (p